2021
DOI: 10.1016/j.ijid.2020.10.085
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic plasma exchange followed by convalescent plasma transfusion in critical COVID-19—An exploratory study

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
64
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 12 publications
4
64
0
1
Order By: Relevance
“…On the other hand, CP therapy is commonly used in infectious diseases [ 10 , 27 ]. CP is enriched with neutralizing antibodies against certain infectious agents and could be beneficial in controlling the infectious agent [ 32 ]. So, the purposes of PE therapy and CP therapy are different.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CP therapy is commonly used in infectious diseases [ 10 , 27 ]. CP is enriched with neutralizing antibodies against certain infectious agents and could be beneficial in controlling the infectious agent [ 32 ]. So, the purposes of PE therapy and CP therapy are different.…”
Section: Discussionmentioning
confidence: 99%
“…After an initial increase, IFN‐γ production decreased again, which could reflect the fact that proinflammatory immune responses shifted to anti‐inflammatory responses 17 . It has already been shown that there was a reduction in proinflammatory cytokines like IL‐6 and an increase in anti‐inflammatory cytokines after CP was administered 18‐20 . Moreover, chronic kidney disease suppressed T‐cell function, which could impede long‐term protection against reinfection 3,21 …”
Section: Discussionmentioning
confidence: 99%
“… 19 Other recent exploratory study reported potential therapeutic benefits of CP in the management of COVID-19. 20 Another study involving a course of high-dose methylprednisolone, with or without Tocilizumab, showed a significant acceleration in respiratory recovery, lower hospital mortality and reduced likelihood of invasive mechanical ventilation in COVID-19-associated cytokine storm syndrome. 21 However, no longitudinal studies were reported in the current literature that compared the use of CP or Tocilizumab or both.…”
Section: Discussionmentioning
confidence: 99%